The Use of Inflectional Suffixes by Third Year English Undergraduates at the College of Education, University of Mosul - Adday Mahmood Adday (PROSPECTIVE RESEARCHES, 2023)
This research deals with the inflectional suffixes in English with reference to the derivational suffixes that basically change the function and the meaning of the base in award. The aim of this research is to focus on the inflectional suffixes explaining the different types of these suffixes that are basically added to the final syllable of award only. A test was made for the standard of third year students of each type of these suffixes that end award by adding just one type of the basic nine inflectional suffixes. This research , after that, focuses on the inflectional suffixes in which the students of the third year have answers that are less than what is expected so as to handle and give the suitable suggestions for foreign learners of English in general, and for the students of the third year in particular, and solutions for the students in order not to commit the same errors in the future referring to the approaches and methods that are used by the countries that use English language in solving these errors.